Comparative study on the composition of free amino acids and derivatives in the two botanical origins of an edible Chinese herb "Xiebai", i.e., Allium chinense G. Don and Allium macrostemon Bunge species. (April 2018) - He, Quan; Huang, Shaohui; Wu, Yuehong; Zhang, Wenqi; Wang, Fanchao; Cao, Jiawei; Sheng, Qing; Liang, Zongsuo; Liu, Lili; Ou, Wen-Bin
Abstract: Xiebai is an edible Chinese herb with various health and therapeutic benefits. To evaluate its nutritional and health values, the free amino acids and derivatives of its two botanical origins (i.e., Allium chinense G. Don and Allium macrostemon Bunge) were isolated using a solvent extraction method and analyzed using automatic amino acid analysis and ultra-performance liquid chromatography-quadrupole-time of flight (UPLC-Q-TOF) mass spectrometry. Our data show that both plants contain abundant free amino acids, and the amount of total free amino acids in A. chinense G. Don is higher than that in A. macrostemon Bunge. The free amino acid compositions in the two plants are qualitatively similar, including nineteen proteinogenic and four non-proteinogenic amino acids. The identified proteinogenic amino acids include eight essential amino acids and five semi-essential amino acids. The sum of essential and semi-essential amino acids accounts for 64.9% and 69.7% of the total free amino acids of the two plants, respectively. The principal amino acids of both plants, from highest concentration to lowest concentration, are arginine, glutamine, glutamic acid, asparagine and serine. A. chinense G. Don is also rich in citrulline and lysine. In addition, two amino acid derivatives were identified from the two plants, i.e., the proline analog N ‑methyl‑proline and the dipeptide H-Glu-Tyr-OH. For the first time, the presence of N ‑methyl‑proline in the plants of the Allium genus and the presence of H-Glu-Tyr-OH in unprocessed food sources are reported. The influences of the identified substances on the flavor, nutrition and health values of Xiebai are discussed. Graphical abstract: Unlabelled Image Highlights: Free amino acids and derivatives in an edible Chinese herb Xiebai were determined. The principal amino acids in Xiebai are Arg, Gln, Glu, Cit, Lys, Asn and Ser. For the first time, N ‑methyl‑proline was discovered in Allium plants. For the first time, H-Glu-Tyr-OH was discovered in unprocessed food sources. The identified substances affect the flavor, nutrition and health values of Xiebai .